A novel necroptosis-related model predicts the prognosis and immunocompetence of head and neck squamous cell carcinoma: A Novel model predicts the prognosis of HNSCC - Zhang, Jixia; Wang, Anli; Qiu, Lin (Cellular and Molecular Biology, 2023)
Head and neck squamous cell carcinoma (HNSCC) is a disease characterized by profound immunosuppression and the prognosis of HNSCC patients remains poor. Necroptosis is a programmed lytic cell-death mechanism that can promote tumor growth, angiogenesis, invasion and metastasis. The differentially expressed NRGs were screened by using the LIMMA package of R software (version 4.1.2) and the prognosis-related NRGs were obtained by COX regression analysis. We separated patients into high- and low-risk groups via the prognostic model consisting of those NRGs. The receiver operating characteristic (ROC) curve and Kaplan-Meier survival curves were used to validate the prognostic model. By bioinformatics analysis, the prognostic risk and immunocompetent models were constructed. We reevaluate the prognostic model based on the GES27020 data sets, clinicopathological variables and chemotherapeutic efficacy. Individuals in the high-risk group had much shorter overall survival (OS) times than their counterparts. Compared with clinicopathological variables, the risk model has a higher diagnostic efficiency, with the area under the ROC being 0.699. Decision Curve Analysis (DCA) showed the prognostic model-based risk score was the superior prognostic factor compared to additional indicators. Furthermore, the high- and low-risk groups had differences in immune cell infiltration and immune functions. And the CCK-8 showed that small molecular drugs could inhibit HNSCC cell proliferation in vitro. We have constructed a new necroptosis-related model, which can be used to predict the prognosis and immunocompetence of HNSCC patients and provide a theoretical basis for the study of necroptosis in the clinical prognosis of HNSCC.